2022
DOI: 10.1111/pin.13287
|View full text |Cite
|
Sign up to set email alerts
|

Development of extrahepatic bile ducts and mechanisms of tumorigenesis: Lessons from mouse models

Abstract: The biliary system is a highly branched tubular network consisting of intrahepatic bile ducts (IHBDs) and extrahepatic bile ducts (EHBDs). IHBDs are derived from hepatic progenitor cells, while EHBDs originate directly from the endoderm through a separate branching morphogenetic process. Traits that are important for cancer are often found to overlap in developmental and other processes. Therefore, it has been suggested that intrahepatic cholangiocarcinomas (iCCAs) and extrahepatic cholangiocarcinomas (eCCAs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…It has been suggested that intraductal papillary neoplasm of bile duct (IPNB) derived from PBGs are preneoplastic lesions of mucin-producing CCAs that morphologically resemble PBGs [68]. Interestingly, interleukin (IL)-33-mediated biliary epithelial injury-induced regenerative response accelerates the development of extrahepatic CCA from peribiliary glands, as demonstrated by lineage tracing models [69,70]. The role of PBGs in the genesis of ampullary tumors has been demonstrated in lineage tracing models [71].…”
Section: Lineage-based Carcinogenesismentioning
confidence: 99%
“…It has been suggested that intraductal papillary neoplasm of bile duct (IPNB) derived from PBGs are preneoplastic lesions of mucin-producing CCAs that morphologically resemble PBGs [68]. Interestingly, interleukin (IL)-33-mediated biliary epithelial injury-induced regenerative response accelerates the development of extrahepatic CCA from peribiliary glands, as demonstrated by lineage tracing models [69,70]. The role of PBGs in the genesis of ampullary tumors has been demonstrated in lineage tracing models [71].…”
Section: Lineage-based Carcinogenesismentioning
confidence: 99%
“…The gallbladder, the extrahepatic biliary ducts (EHBDs), the liver, and the pancreas all develop from an outpouching of the endodermal lining of the foregut called the hepatic diverticulum. SOX17, along with Pdx1, plays a decisive role in whether Pdx1+ cells are differentiated towards the pancreas or EHBD; SOX17 expression promotes biliary tract formation, while SOX17 haploinsufficiency in mice leads to gallbladder and EHBD hypoplasia [69].…”
Section: Gallbladder and Extrahepatic Bile Ductsmentioning
confidence: 99%